INNOVATIVE APPROACH TO IMPROVEMENT OF THE PROFESSIONAL AND APPLIED SECTION OF PHYSICAL CULTURE IN UNIVERSITY USING MEANS OF SINGLE COMBATS - Peredelskiy, A.A.; Akhapkin, V.N.; Malinin, A.N.; D.V. Sorokin (Theory and Practice of Physical Culture, 2023)
Objective of the study is the scientific and theoretical substantiation of the professionally applied section of physical culture at the university, based on martial arts. Methods and structure of the study. Within the framework of the scientific experiment, the curriculum was supplemented with a professional-applied section aimed at the formation of applied knowledge, the development of skills and abilities of a practical orientation, as well as the education of the leading psychophysical, social and personal qualities of future specialists. Various types of martial arts act as an effective means of high school professionally applied physical culture. In the course of the study, a survey and an experiment were conducted, in which students of the Russian Timiryazev State Agrarian University, divided into control and experimental groups of 20 people each. The control group was engaged in the traditional curriculum in physical culture, the experimental group - in the innovative program with the inclusion of an applied section related to martial arts. Results and conclusions. As the results of the study showed, an innovative curriculum aimed at using martial arts technologies based on spiritual historical practices, transferring the elements of motor actions of martial artists into the physical readiness of future specialists, allows you to effectively form applied knowledge, skills, and educate psychophysical, social and personal qualities.